Cochlear implantation in children with labyrinthitis ossificans - Abdullah A,; Shaharudin MH,; Ami M,; Awang MA,; Marhaban JA,; Othman BF,; Zulfiqar MA,; Saim L, (Penerbit UKM, 2006)
Evidence of ossification was previously considered a relative contraindication to cochlear implantation. It was considered difficult or impossible to achieve safe electrode insertion because of bony obstruction. Either the electrodes or the inner ear structures could be damaged. Moreover, obstructed scala tympani could limit the number of electrodes that can be inserted. The efficacy of the electrical stimulation was also questioned, as a higher current would be needed on an ossified cochlea. Finally, the neural survival in ossified cochlea is unknown. This may complicate the surgical procedure and affect the long-term outcome. However, depending on the experience of the surgeon, cochlear implantation has been attempted even in grossly ossified cochlea. Here we illustrate that cochlear implantation is safe in labyrinthitis ossificans